DESIGN MANAGEMENT IN TODAY’S BUSINESS: A REVIEW - Mutiara, Maitri Widya; Irawan, Agustinus Purna; Marizar, Eddy Supriyatna (Graduate Program of Universitas Tarumanagara, 2023)
Design is a part of business that cannot be separated from human life today. From business products to service industries, design has been used as part of improving competitive advantage or finding solutions to problems faced. Design can no longer be seen as just an aesthetic companion, but has broader role to play. With the design industry is currently quite in demand, it can be seen in the development of fields in the field of design or jobs that require design. For this reason, design management is indispensable. Management and design are complementary fields in the process. In this initial study research, the researcher wanted to prove the assumption of design management in the business industry, as well as to get an initial model of Design Management. This research is qualitative research by conducting desk-research and a multi-disciplinary approach, which are design and management, through the study of management functions, management strategies, the design process becomes a reference in this research, to become a starting point for Design Management research. The main activity of this research is a literature study of previous research that resulted in an initial model of Design Management.